Analysis of the Effectiveness of Using Shopee as a Marketing Means for Sales of Naruna Food Products at PT. Naruna Karya Bersama - Laksono, Rachmad Budi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Information technology is one of the many important things needed for business development in Indonesia. This research aims to analyze the effectiveness of sales through Shopee merchants by looking at the effect of cashback and free shipping on whether they can influence sales of Naruna Food products. The sampling technique used was convenience. with 100 respondents designated as samples. The questionnaire method is a method for collecting data in this research. The data analysis technique for this research uses Partial Least Square (PLS). The research results show that cashback and free shipping have a significant effect on product sales. This can be interpreted that the increasing cashback and free shipping will also increase product sales of Naruna Food Products at PT. Naruna Karya Bersama.